Sunny makes her case - Holm, Jennifer L. (New York, NY Graphix, an imprint of Scholastic, 2024)
Sunny is starting to understand the ins and outs of middle school... but she still feels more out than in. It's about classes or homework, really. No, it's the fact that most kids have a thing they do outside of class. Like football or track or cheerleading. Sunny isn't quarterback material, and her cheer attempts are... not the best. So what can she do? When Sunny's friend Arun says he wants to start a debate club, she's not really sure what he means. Isn't debate just... arguing? Sunny's never had a problem with arguing. Arun and the advisor show her there's more to it than that -- there's also teamwork, and research, and being able to speak up in front of judges. Some of the debates are fun ones -- which is the best candy? Is peanut butter a force for evil or a force for good? But when the debate club starts to be a success, Sunny realizes she won't just be able to talk her way into winning... she'll have to make her case! --Back cover.
Ages 8-12